Longitudinal electron bunch profile reconstruction by performing phase retrieval on coherent transition radiation spectra - Bajlekov, S; Heigoldt, M; Popp, A; Wenz, J; Khrennikov, K; Karsch, S; Hooker, S (2013)
The application of phase-retrieval algorithms to the reconstruction of the longitudinal bunch profile of an electron bunch from the spectrum of the coherent transition radiation (CTR) it produces is considered. The development of a new algorithm for this application, the Bubblewrap algorithm, is described. Tests with synthetic data show successful reconstruction of the longitudinal profile of single and double electron bunches, provided that the CTR spectrum is known over a sufficiently wide range. The application of the Bubblewrap algorithm to the reconstruction of laser-accelerated electron bunch profiles from experimental data is demonstrated. The results are shown to be consistent with estimates of the bunch length obtained by other methods.© http://creativecommons.org/licenses/by/3.0/Creative Commons Attribution 3.0 License. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.